Digital Marketing Strategy to Increase MSME Sales in the Digital Age - Kusnadi (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
Digital marketing is a marketing strategy that uses digital platforms and channels to promote a product, service or brand. In the modern business world, digital marketing has become an integral component in marketing efforts because it utilizes digital technology and the internet. This study aims to determine the effect of digital marketing on sales, marketing strategies, and obstacles in implementing digital marketing in MSME players using descriptive qualitative research methods. The results of this study discuss the importance of digital marketing strategies in increasing sales of MSMEs, with a focus on Es Dawet Wong Ndeso in Sleman, Yogyakarta. Digital marketing utilizes digital platforms, tools, and analytics techniques to effectively reach target audiences. The internet is becoming a powerful, affordable, and effective online digital marketing hub. Digital marketing expands sales share and presents various methods to sell, advertise, and display products. The implementation of digital marketing has a significant impact on MSME sales, but is faced with several obstacles such as limited understanding, online fraud, fierce competition, unstable internet connections, problems with suppliers, and increased product delivery time to consumers. Therefore, MSME players need to pay attention to digital marketing strategies and overcome the obstacles that arise. The decision to use digital marketing as a business strategy needs to be adjusted to the specifications of the company being adopted to ensure the suitability of strategy implementation.